A nation within a nation : Amiri Baraka (LeRoi Jones) and Black power politics - Woodard, Komozi (University of North Carolina Press, 1999)
Poet and playwright Amiri Baraka is best known as one of the African American writers who helped ignite the Black Arts Movement. This book examines Baraka's cultural approach to Black Power politics and explores his role in the phenomenal spread of black nationalism in the urban centers of late-twentieth-century America, including his part in the election of black public officials, his leadership in the Modern Black Convention Movement, and his work in housing and community development.